Morphology transition of the primary silicon particles in a hypereutectic A390 alloy in high pressure die casting. Issue 1 (December 2017) - Wang, J.; Guo, Z.; Song, J.; Hu, W.; Li, J.; Xiong, S.
Abstract The microstructure of a high-pressure die-cast hypereutectic A390 alloy, including PSPs, pores, α-Al grains and Cu-rich phases, was characterized using synchrotron X-ray tomography, together with SEM, TEM and EBSD. The Cu-rich phases exhibited a net morphology and distributed at the boundaries of the α-Al grains, which in turn surrounded the PSPs. Statistical analysis of the reconstructed 1000 PSPs showed that both equivalent diameter and shape factor of the PSPs exhibited a unimodal distribution with peaks corresponding to 25 μm and 0.78, respectively.) PSPs morphology with multiple twinning were observed and morphological or growth transition of the PSPs from regular octahedral shape (with a shape factor of 0.85 was mainly caused by the constraint of the Cu-rich phases. In particular, the presence of the Cu-rich phases restricted the growth of the α-Al grains, inducing stress on the internal silicon particles, which caused multiple twinning occurrence with higher growth potential and consequently led to growth transitions of the PSPs.